FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA KEKAMBUHAN PADA PENDERITA GANGGUAN JIWA DI WILAYAH KERJA PUSKESMAS SUNGAI DAREH KABUPATEN DHARMASRAYA - Yuli Permata Sari; Vivi Nofita Sapitri; Yaslina Yaslina (JURNAL KESEHATAN PERINTIS, 2018)
Mental disorders are a group of psychotic disorders, with a basic disorder of personality, a distinctive distortion of thought processes. Based on WHO data in 2015 the prevalence of mental disorders is 465 million in the world. Civil Registry Agency (BPS) 2015, the prevalence of people with mental disorders Indonesia reached 15.3% of the 259.9 million inhabitants of Indonesia. Based on data from Health Research Association (RISKESDAS) West Sumatera Province in 2015 mentions the prevalence of mental disorders 1.9 per mile. In the working area of ​​Puskesmas Sungai Dareh Dharmasraya district mental disorders increase annually where during the year 2015 is about 47 people, and in 2016 about 49 people. The purpose of this study is to determine "Factors associated with the occurrence of recurrence in people with mental disorders in the Work Area Puskesmas River Dareh Dharmasraya Regency Year 2017. This research method using descriptive analytic methods and methods Crosecsional study. The sample in this study were 40 respondents. This study was conducted on March 1 to 10, 2018. The result of medication compliance statistic test obtained p value = 0,000 (p <α), family support obtained p value = 0.001 (p <α), health officer support obtained p value = 0.000 (p <α) it can be concluded the existence of drug adherence compliance factor factor, family support and health officer support with the occurrence of recurrence in people with mental disorders in the Work Area Puskesmas River Dareh Dharmasraya Regency in 2017. It is suggested to the researchers then can research in different places, more samples, and conducted more in-depth research such as research with guided interviews.